(untitled) (Research, Society and Development, 2022)
Studies in different countries indicate that students and health professionals have difficulties in seeking scientific information for academic and clinical use. This article aims to present the main intellectual stages of information search for clinical and academic purposes, as well as the possibilities and challenges that arise in each of the stages. We used a descriptive qualitative design based on a selective literature review, presentation of practical examples and some solutions to doubts related to health information seeking. The following stages of information search were presented: defining what the researcher wants to know; transforming the PICO research question into a database search strategy; defining where to search for the information; sources used in the health field for clinical and/or academic purposes. The process of information search demands specific intellectual decisions for each clinical or research situation. Therefore, just following information search manuals may not be enough to achieve a satisfactory result. It is necessary to bring to the level of consciousness the objectives of the search, the choice of sources, and the selection of the best information to answer the initial research question.